Learning strategies to develop reading and writing skills in second grade at Rubén Dario Primary School, 2022 / Mercedes Anielka Bermúdez Aguinaga, Cristina Janeth Pérez - Bermúdez Aguinaga, Mercedes Anielka (2022)
In this research about learning strategies to develop reading and writing skill was done at Rubén Dario school with student of second grade at Siuna city, RACCN Nicaraguan. the purpose was identifying the different kind of strategies that teacher uses to promote reading and writing skill. Furthermore, to consider some implemented strategies give not good results due to, the student's behavior that have that day for instance the change of mood. but it is important to follow looking new strategies to encourage them and they get engage the scholar activities. This research was done across of techniques applied were such as: observation guide, interview and focus group, qualitative paradigm way with descriptive ethnomethodological approach and depth level for the data collection. Throught of these techniques we achieve to found some learning strategies of learning to develop reading skill we were able to identify some strategies of teaching that the teacher applied using flashcards. He starts promoting the pronunciation of the vocabulary, and then he used main strategies such as math to the picture to the word, unscramble words and complete the blank space to developing reading and writing skill the children enjoyed to do it. Thus, the teacher was using flashcard to develop literacy but some students have weakness in this skill, so, they tend to confuse because the writing and reading its different in English. In addition, the parents have not knowledge related to this foreign language it affects the development of their increase in these skills. On the other hand, there are many learners in the classroom avoiding to make different activities around there, also lack of didactic materials affect the learning process. Based on this, we propose to use some learning strategies considering that are useful to implement during the development of class and so, strengthen the reding and writing skills. These strategies are: magic box, scattergories and fishbowl game.